تحليل الأخطاء في تعليم اللغة العربية بالمدرسة الثانوية الإسلامية الحكومية السادسة آتشية بسار - Safitri, Ema; Fairouz, Liza (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
Error analysis is a crucial component in teaching foreign languages, including Arabic. This study aims to identify, analyze, and classify linguistic errors made by 12th-grade students at MAN 6 Aceh Besar. Data were collected through observations, tests, and documentation involving 20 students as the sample. The results indicate that the most prevalent errors include grammatical errors, vocabulary misuse, and spelling mistakes. The contributing factors include first-language interference, insufficient understanding of Arabic grammatical rules, and lack of practical exercises in speaking and writing. Based on these findings, this study provides recommendations for educators to enhance teaching strategies effectively. تحليل الأخطاء هو عنصر أساسي في تدريس اللغات الأجنبية، بما في ذلك اللغة العربية. تهدف هذه الدراسة إلى تحديد الأخطاء اللغوية التي يرتكبها طلاب الصف الثاني عشر في MAN 6 آتشيه بَسَار، وتحليلها وتصنيفها. تم جمع البيانات من خلال الملاحظات والاختبارات والتوثيق، بمشاركة 20 طالبًا كعينة للدراسة. تشير النتائج إلى أن أكثر الأخطاء شيوعًا تشمل الأخطاء النحوية، وسوء استخدام المفردات، والأخطاء الإملائية. وتشمل العوامل المساهمة في هذه الأخطاء تأثير اللغة الأم، وعدم الفهم الكافي لقواعد النحو العربي، ونقص التدريبات العملية في التحدث والكتابة. بناءً على هذه النتائج، تقدم هذه الدراسة توصيات للمعلمين من أجل تعزيز استراتيجيات التدريس بفعالية.